2018
DOI: 10.1155/2018/4793174
|View full text |Cite
|
Sign up to set email alerts
|

A Shallow Angle Short-Axis Out-of-Plane Approach Reduces the Rate of Posterior Wall Injuries in Central Venous Catheterization: A Simulation Study

Abstract: The short-axis out-of-plane approach (SAX-OOP) is commonly used in ultrasound-guided internal jugular vein catheterization. However, this approach has a risk of posterior vein wall injuries. The authors hypothesized that a shallow angle of approach may reduce the rate of posterior wall injuries compared with the conventional steep angle approach. The present study aimed to evaluate whether a difference in the angle of approach of the needle affects the rate of posterior wall injuries. The present study was a r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 11 publications
(14 citation statements)
references
References 14 publications
0
14
0
Order By: Relevance
“…Sample size calculation. A previous study showed that the incidence of posterior vin wall injury is 41% using a steep angle of approach and 9% with a shallow angle of approach [5]. Based on this data the sample size required for 80% power at ɑ = 0.05 was estimated to be thirty-four participants and we planned to include thirty-five junior residents as participants.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Sample size calculation. A previous study showed that the incidence of posterior vin wall injury is 41% using a steep angle of approach and 9% with a shallow angle of approach [5]. Based on this data the sample size required for 80% power at ɑ = 0.05 was estimated to be thirty-four participants and we planned to include thirty-five junior residents as participants.…”
Section: Discussionmentioning
confidence: 99%
“…Potential participants with prior experience performing central venous catheterization with using a needle guide were excluded. Sample size was calculated using a previous study [5] which is described below in the statistical analysis section.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations